Value Factors, Capture Prices and Cannibalism: nightmares for renewable energy decision-makers. (31st May 2021) - Blume-Werry, Eike; Huber, Claus; Resch, Gustav; Haas, Reinhard; Everts, Martin
Abstract: Renewable energy sources increasingly seek to compete in electricity markets outside of traditional support schemes. In this context, market values and the cannibalization risks of wind and solar photovoltaic (PV) take on crucial roles for investment decisions and potential investors. Most existing studies analyse the market value of renewables at different penetration levels, looking at the extent to which PV panels and wind turbines cannibalize their own market revenues. This article explores how other market and policy drivers affect wind and PV value factors and capture prices in real-world settings over the next three decades. To this end, we model and analyse a number of scenarios with altered natural gas, coal and carbon prices as well as varied availabilities of wind and PV in Europe. We find that higher natural gas and carbon prices result in lower wind and PV value factors and vice versa, while the influence of coal prices is rather limited. Our results show substantial merit order effects on absolute wind and PV capture prices, following varied availabilities yet no significant cross-cannibalization between the two technologies.